Protective Efficacy of a Mucosal Influenza Vaccine Formulation Based on the Recombinant Nucleoprotein Co-Administered with a TLR2/6 Agonist BPPcysMPEG - Maria Victoria Sanchez; Thomas Ebensen; Kai Schulze; Diego Esteban Cargnelutti; Eduardo A. Scodeller; Carlos A. Guzmán (MDPI AG, 2023)
Current influenza vaccines target highly variable surface glycoproteins; thus, mismatches between vaccine strains and circulating strains often diminish vaccine protection. For this reason, there is still a critical need to develop effective influenza vaccines able to protect also against the drift and shift of different variants of influenza viruses. It has been demonstrated that influenza nucleoprotein (NP) is a strong candidate for a universal vaccine, which contributes to providing cross-protection in animal models. In this study, we developed an adjuvanted mucosal vaccine using the recombinant NP (rNP) and the TLR2/6 agonist S-[2,3-bispalmitoyiloxy-(2R)-propyl]-R-cysteinyl-amido-monomethoxyl-poly-ethylene-glycol (BPPcysMPEG). The vaccine efficacy was compared with that observed following parenteral vaccination of mice with the same formulation. Mice vaccinated with 2 doses of rNP alone or co-administered with BPPcysMPEG by the intranasal (i.n.) route showed enhanced antigen-specific humoral and cellular responses. Moreover, NP-specific humoral immune responses, characterized by significant NP-specific IgG and IgG subclass titers in sera and NP-specific IgA titers in mucosal territories, were remarkably increased in mice vaccinated with the adjuvanted formulation as compared with those of the non-adjuvanted vaccination group. The addition of BPPcysMPEG also improved NP-specific cellular responses in vaccinated mice, characterized by robust lymphoproliferation and mixed Th1/Th2/Th17 immune profiles. Finally, it is notable that the immune responses elicited by the novel formulation administered by the i.n. route were able to confer protection against the influenza H1N1 A/Puerto Rico/8/1934 virus.